The Company’s Fianacial Achievement Is Influenced By Intellectual Capital - Ranitawati, Endang (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2021)
The purpose of this study is to detect the financial performance of companies in the financial sector that is influenced by intellectual capital. Secondary data of companies in the financial sector listed on the IDX for the period 2017-2019 became the source of research data and were analyzed using the partial least square (PLS) analysis method. This study shows the results that the company’s financial performance is negatively affected by HCE, but is positively influenced by SCE and CEE. While the participation of IC has a significant effect on financial performance, there is no distinction between distinct sub-sectors.